A pragmatic analysis of discourse particles in Filipino computer mediated communication - Palacio, May Antonette; Gustilo, Leah (Penerbit Universiti Kebangsaan Malaysia, 2016)
As the English language continues to evolve through time, many of its structures and functions changed, which made it even realizable that the smallest unit in a discourse can play a crucial role in communication. Hence, this present study is an attempt to investigate the phenomenon and further delve into the discourse-pragmatic functions of discourse particles (DPs) in digital genres, particularly on Facebook, since DPs are commonly used by Filipino youths when posting and commenting online. Thirty tertiary-level students from different universities in Metro Manila, Philippines, were selected to participate in the present study. Using both qualitative and quasi-quantitative methods, results revealed a surprising number and interesting types of combined English and Filipino Relational DPs having several micro functions. Generally, they serve as a device that can let the interlocutors convey their emotions, relationships, and attitudes towards the receiver of their message. Discourse particles have crucial and prominent implications in the way Filipinos, particularly the youth, express their message, gain understanding of the received message, and establish speakerreceiver relationships and attitude on Facebook.